Pengaruh Label Halal Dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen - Arifin; Kohar; Purwanto (Jurnal Bisnis Darmajaya, 2025)
This research aims to find out whether there is an influence of halal labels and product quality on consumer purchasing decisions at Dapur Azka. This research uses quantitative methods with sampling using non-probability sampling techniques with purposive sampling. The sample in this research was 96 Dapur Azka consumers. The results of data analysis using SPSS Version 20 show that the halal label has a positive and significant effect on consumer purchasing decisions. Every increase in the halal label factor by 1 unit will increase purchasing decisions by 0.213 units. Apart from that, there is a positive and significant influence of product quality on purchasing decisions. It was found that product quality was able to influence purchasing decisions by 1,099 units. Simultaneously, the halal label and product quality have a very high influence of 97.2% on consumer purchasing decisions. This shows the importance of these factors in influencing the purchasing decisions of Dapur Azka consumers. It can be concluded from the results of this research that the halal label variables and product quality have a positive and significant effect on consumer purchasing decisions at Dapur Azka.